Brolucizumab for recalcitrant macular neovascularization in age-related macular degeneration with pigment epithelial detachment: original research article - Chronopoulos, Argyrios; Huynh, Elisa; Ashurov, Agharza; Schutz, James S; Jonas, Jost B.; Hattenbach, Lars-Olof (European journal of ophthalmology, 2024)
Purpose - To analyze anatomic and functional response to intravitreal brolucizumab in age-related macular degeneration recalcitrant to previous intravitreal anti-VEGF therapies. - Methods - In this monocentric, one arm, retrospective study, eyes affected by neovascular age-related macular degeneration (nAMD) resistant to other intravitreally injected anti-vascular endothelial growth factor inhibitors were switched to intravitreal brolucizumab. All patients underwent ophthalmological examinations at baseline and in regular follow-up intervals. Best registered visual acuity (BRVA), Goldmann tonometry, intraocular pressure (IOP), central retinal thickness (CRT) and pigment epithelial detachment (PED) characteristics were analyzed at initiation of anti-VEGF treatment, at treatment switch, and at the end of brolucizumab loading phase. - Results - The study included 20 eyes of 18 consecutively treated patients (age: 77 ± 6 years). All eyes had macular neovascularization with PED. Previous treatments included intravitreal aflibercept, bevacizumab, and ranibizumab and had not resulted in a significant improvement in BRVA (0.5 ± 0.5 logMAR vs 0.5 ± 0.6 logMAR) or mean CRT (320 ± 60 µm vs 313 ± 83 µm) up to treatment switch to brolucizumab. At the end of the brolucizumab loading phase, there was significant improvement for both BRVA (0.3 ± 0.2 logMAR, P < 0.05) and CRT (264 ± 55 µm, P < 0.05). Under previous anti-VEGF therapy, there was a significant increase/deterioration in both PED area (2.68 mm2 to 5.18 mm2, P < 0.05) and PED volume (0.39 mm3 to 1.07 mm3, P < 0.05); however, both parameters improved after switching to brolucizumab (3.81 mm2 and 0.37 mm3, P < 0.05). - Conclusion - Our results suggest a favourable anatomical and visual response after treatment switch to brolucizumab in patients with nAMD refractory to previous anti-VEGF agents.
Online veröffentlicht: 18. Juli 2023
Gesehen am 20.02.2024